FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ACNE VULGARIS (JERAWAT) PADA REMAJA DI SMK TARUNA PEKANBARU TAHUN 2014 - HASTUTI MARLINA; HETTY ISMAINAR (JURNAL PROTEKSI KESEHATAN, 2015)
Acne vulgaris is a chronic inflammatory disease of the follicles pilosebaseous, characterized by comedones, papules, pustules, and nodules.The main causes of acne as yet known with certainty, but there is strong suspicion is a multifactorial disease, including heredity, hormonal balance, diet, skin condition and hygiene. Acne is a skin disease that is often found in adolescents by (85%).. Based on the results of the survey in 5 SMK Pekanbaru on class X , obtained the highest number of cases of acne that is in SMK Taruna Pekanbaru many as 113people. This study aims to determine the factors associated with the incidence of acne vulgaris in adolescents in SMK Taruna Pekanbaru 2014. The research is quantitative cross-sectional study research design that was held on 5-9 May 2014, in SMK Taruna Pekanbaru. The population this is the entire student SMK Taruna Pekanbaru class X at 302 people, and obtained a large sample of 117people, with rendom systematic sampling technique using a questionnaire measuring instruments. Data analiysis of univariate and bivariate using chi square test.The results showed that there is a relationship of knowledge obtainable, (p value = 0,006 dan POR = 3,06, 95%CI : 1,43-6,75), foods that can emergence the onset of acne obtainable (p value = 0,009 and POR = 2,88, 95%CI : 1,35-6,14, the frequency of facial wash (cleaning) obtainable (p value = 0,009 and POR = 2,88, 95%CI : 1,35-6,14) and the condition of facial skin obtainable (p value = 0,005, POR = 3,12 , 95%CI : 1,46-6,68) with incidence of acne vulgaris. It is recommended for adolescents to avoid foods that can emergence the onset of acne, skin treatment to reduce excess oil production by applying frequency facial wash (cleaning) on a regular basis.